University of the Future: Re-Imagining Research and Higher Education 2020
DOI: 10.29117/quarfe.2020.0282
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Trust in Government Modify: The association between Mental Health and Stringency of Public Health Measures to reduce COVID-19

Abstract: Introduction: Trust in government to take care of its citizens may affect mental health outcomes such as anxiety and depression, particularly as measures become more stringent. The study aimed to investigate the associations between stringency of COVID-19 social distancing policies and mental health outcomes, and the moderating effects of trust in government and gender. Methods: The study consisted of secondary analysis of publicly available cross sectional data from a global online survey COVID-19 survey cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The lack of an effect of the stringency of the COVID-19 policies on QoL may be explained by the fact that our study took place during the second wave of the pandemic. Previous studies that were conducted during the initial phase, or its aftermath (summer 2020), have reported either negative ( O’Hara et al, 2020 ; Lee et al, 2021a ; Voss et al, 2021 ), or positive effects on individuals’ mental health ( Kim and Jung, 2021 ; Lee et al, 2021b ; Long et al, 2021 ). Hence, current findings may indicate that, over time, individuals became more resistant to fluctuations in policies and restrictions, possibly because they had become accustomed to the uncertainty and frequent policy changes.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an effect of the stringency of the COVID-19 policies on QoL may be explained by the fact that our study took place during the second wave of the pandemic. Previous studies that were conducted during the initial phase, or its aftermath (summer 2020), have reported either negative ( O’Hara et al, 2020 ; Lee et al, 2021a ; Voss et al, 2021 ), or positive effects on individuals’ mental health ( Kim and Jung, 2021 ; Lee et al, 2021b ; Long et al, 2021 ). Hence, current findings may indicate that, over time, individuals became more resistant to fluctuations in policies and restrictions, possibly because they had become accustomed to the uncertainty and frequent policy changes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Filipinos who believe that the public institutions are capable of responding effectively to the COVID‐19 crisis are less likely to experience emotional distress, which, in turn, can lead to a better quality of life. Indeed, recent transnational research involving participants from 58 countries showed that individuals who have higher trust in their government reported lower depression and anxiety during the COVID‐19 crisis (O'Hara et al, 2020 ). Consistent with our findings on distress as an underlying mechanism predicting quality of life, facing emotional distress during the COVID‐19 pandemic was found to lead to a significant decrease in quality of life among Vietnamese with suspected COVID‐19 symptoms (Nguyen et al, 2020 ), and among COVID‐19 patients, frontline nurses, and residents in China (An et al, 2020 ; Ma et al, 2020 ; Zhang & Ma, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that since policies and measures in responding to the COVID‐19 pandemic in the Philippines are created and implemented by public institutions, Filipinos' perceived effectiveness of public institutions' crisis response protocol is a critical protective factor against psychological distress and poor quality of life in the days of a global pandemic. Indeed, building safety and trust could alleviate distress and promote recovery (Li et al, 2011 ; O'Hara et al, 2020 ) and may serve as a building block for a better quality of life (Zhang & Ma, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we included individuals’ perceptions of how likely they were to contract COVID-19 and 2 interaction terms: gender and the level of trust in PHAs; and age and the presence or absence of a preexisting condition that increases COVID-19 vulnerability. We hypothesized from previous literature that women would be more likely than men to take precautions if they had a high level of trust in PHAs [ 27 , 28 ] and that older adults with preexisting conditions would be more likely to take precautions than their younger counterparts [ 29 ]. All of these variables and their levels of measurement are described in the beginning of the Results section below.…”
Section: Methodsmentioning
confidence: 99%